Inklusionsorientierte Lehr-Lern- Bausteine für die Hochschullehre Ein Konzept zur Professionalisierung zukünftiger Lehrkräfte - Moser, Vera (Interdisziplinäre Beiträge zur Inklusionsforschung herausgegeben von Marina Egger, Julia Frohn, Vera Moser und Detlef Pech, 2020)
Good inclusive teaching needs teachers who are able to plan and implement pedagogical offers in a heterogeneity-sensitive and adaptive way - however, in university teacher training there are only a few subject-didactically implementable contents for this so far. This book presents five flexibly applicable teaching-learning modules on central topics of inclusive teaching, which were developed by subject didacticians in cooperation with rehabilitation scientists and language educators for university teaching. Starting from the theoretical foundations, the structure, content and materials of the individual teaching-learning modules are presented and commented on didactically. Following on from this, the empirical results of the quantitative and qualitative accompanying evaluation of corresponding courses are analysed. In addition, the suitability of the teaching-learning modules for stabilisation in the university context as well as their possible use in the second and third phase of teacher training are discussed. This book aims to motivate lecturers to use the presented modules in their teaching. It is also aimed at students, researchers and teachers who want to develop their teaching in an inclusive way.